The Use of Plants for Fencing and Fuelwood in Mustang District, Trans-Himalayas, Nepal - Bhattarai, Shandesh; Chaudhary, Ram P; Taylor, Robin SL (Scientific World, 2010)
The remoteness and difficult geography of Mustang in trans-Himalayas lead to continued use of wild plants for livelihood. Local people were interviewed during 2005-2007 and we recorded the use of 40 plant species belonging to 14 families under 22 genera as fence and fuelwood. The common parts of the plants used for fence and fuelwood are stems, branches and whole plant. Among 40 plant species, 36 species were used for fencing and 38 species as fuelwood. A total of 30 species with medicinal value were used as fence after cutting. Many plant species have duel uses as fence and fuelwood. In Mustang, suitable plant species are planted live or cut and used as dead fence around agricultural fields to protect the crops from damage by livestock and wild animals as well as prevent soil erosion by wind. Fuelwood is required to cook meals for themselves and feed for livestock, warm homes in the winter, and distil alcohol from the grain. Local communities have preference of using fuelwood on the basis of easy burning, durability and, accessibility and availability. There is need to encourage the practice of using live plant species as bio-fence in Mustang district, in particular in the upper Mustang. Alternative sources of energy have to be explored and practiced to reduce the dependency on fuelwood in upper Mustang for conservation of forest resources. Key words: Plant species; Fencing; Fuelwood; Sustainability. DOI: 10.3126/sw.v7i7.3827 Scientific World Vol.7(7) 2009 pp.59-63